Lignin: An Adaptable Biodegradable Polymer Used in Different Formulation Processes - Andreea Creteanu; Claudiu N. Lungu; Mirela Lungu (MDPI AG, 2024)
Introduction: LIG is a biopolymer found in vascular plant cell walls that is created by networks of hydroxylated and methoxylated phenylpropane that are randomly crosslinked. Plant cell walls contain LIG, a biopolymer with significant potential for usage in modern industrial and pharmaceutical applications. It is a renewable raw resource. The plant is mechanically protected by this substance, which may increase its durability. Because it has antibacterial and antioxidant qualities, LIG also shields plants from biological and chemical challenges from the outside world. Researchers have done a great deal of work to create new materials and substances based on LIG. Numerous applications, including those involving antibacterial agents, antioxidant additives, UV protection agents, hydrogel-forming molecules, nanoparticles, and solid dosage forms, have been made with this biopolymer. Methods: For this review, a consistent literature screening using the Pubmed database from 2019-2024 has been performed. Results: The results showed that there is an increase in interest in lignin as an adaptable biomolecule. The most recent studies are focused on the biosynthesis and antimicrobial properties of lignin-derived molecules. Also, the use of lignin in conjunction with nanostructures is actively explored. Conclusions: Overall, lignin is a versatile molecule with multiple uses in industry and medical science